On the Impact of Risky Private and Public Returns in the Private Provision of Public Goods - The Case of Social Investments - Jana Freundt; Andreas Lange (Center for Economic Studies and ifo Institute (CESifo), 2019)
We use a laboratory experiment to identify the impact of risk in the private and public dimensions of social investments. In variants of a public good game, we separate the return a subject's investment generates for herself vs. the return to others. We find a detrimental effect of risk on public good provision when returns in both dimensions are risky and positively correlated or independent. A negative correlation limits the downside risk and leads to more stable social investments. Disentangling the impact of risk in the two dimensions, we find that investments particularly respond to the risk in the public return dimension.
Keywords: C91; D64; D81; H41; 330; social investments; public goods; giving under risk; correlated risks